Unmet Need of Family-Planning Analysis in Banten Province And Its Determinant Factor : Unmet Need Of Family Planning - Nur Hasanah; Fenita Purnama; Denden Gumilar; Lela Kania Rahsa Puji (STIKep PPNI Jawa Barat, 2021)
Unmet Need is a condition in which it indicates the willingness of fertile couples to one of kinds of contraception devices which is unavailable so that they make a decision not to use device or contraception method.. The purpose of this research was to make a description systematically, factually and accurately, and the correlation of phenomena that were research related to determinant factors of Unmet Need of Family-Planning. This research used cross-sectional design study to find out the determinant factor of Unmet Need use secondary data SKAP BKKBN 2019 as many as 1.656 respondens with univariat, bivariat and multivariat analysis. It has been identified that there is a correlation low education 14,3% and high education 12,2% with incident unmet need family planning, there is a correlation age <20th and >35th as many as 14,6% and age 20th-35th as many as 2,2% with incident unmet need family planning. There is a correlation perception of ideal number of children >2 as many as 10,2% and 6,7% perception of ideal number of children <=2 with incident unmet need family planning. There is a correlation who acces information from media 5% and not acces 9,3% and who acces internet 4% and not acces internet 10,1% with incident unmet need family planning. The variable that most influences the incidence of unmet need from the multivariate results using the backward elimination method is the age of the wife with Exp (B) 7,218. All the variables studied had a correlation with the incidence of unmet need family planning based on seconday data SKAP BKKBN 2019 in Banten Province.